Iridium‐Catalyzed Annulation Reactions of Thiophenes with Carboxylic Acids: Direct Evidence for a Heck‐type Pathway. Issue 21 (23rd April 2018) - Tan, Guangying; You, Qiulin; Lan, Jingbo; You, Jingsong
Abstract: The functionalization of thiophenes is a fundamental and important reaction. Herein, we disclose iridium‐catalyzed one‐pot annulation reactions of (benzo)thiophenes with (hetero)aromatic or α, β‐unsaturated carboxylic acids, which afford thiophene‐fused coumarin‐type frameworks. Dearomatization reactions of 2‐substituted thiophenes with α, β‐unsaturated carboxylic acids deliver various thiophene‐containing spirocyclic products. The occurrence of two interconnected reactions provides direct evidence for a Heck‐type pathway. The mechanistic scenario described herein is distinctly different from the SE Ar and concerted metalation–protodemetalation (CMD) pathways encountered in the well‐described oxidative C−H/C−H cross‐coupling reactions of thiophenes with other heteroarenes. Abstract : In one go : An iridium(III)‐catalyzed annulation reaction of (benzo)thiophenes with (hetero)aromatic or α, β‐unsaturated carboxylic acids provides access to coumarin‐type and spirocyclic frameworks. Direct evidence for a Heck‐type pathway is also presented.